Association of Circulating, Inflammatory Response Exosomal Long RNAs with Ischemic Stroke - Guo-dong He; Shuo Sun; Yu-qing Huang (Frontiers in Bioscience-Landmark)
Background: The expression profiles and function of exosomal long RNAs (exoLRs) in ischemic stroke remain unknown. This study aimed to investigate the pathophysiologic responses reflected by exoLRs. Methods: The expression profile of exosomal messenger RNA, long non-coding RNA and circular RNA in 9 patients with ischemic stroke and 12 healthy individuals were analyzed by sequencing. We assessed the immune cell landscape to reveal the pathophysiologic responses reflected by exoLRs and performed biological process and pathway enrichment analyses. Competing endogenous RNA networks were constructed to explore the molecular functions of exoLRs. Results: A total of 321 up- and 187 down-regulated messenger RNAs, 31 up- and 9 down-regulated long non-coding RNAs, and 67 up- and 48 down-regulated circular RNAs were identified. The immune cell landscape analysis identified that the proportions of exhausted and gamma delta T cells were statistically higher in patients with ischemic stroke. Bioinformatics analyses, including enrichment and competing endogenous RNA network analyses, also indicated that exoLRs were associated with T- cell-mediated inflammatory responses. Conclusions: The expression patterns of exoLRs highlighted the association between ischemic stroke and inflammatory responses mediated by T cells.